Harmonisation or Deregulation? Implementing Equal Pay Law in the European Union and the United Kingdom - Gregory, J (Victoria University of Wellington Law Review, 1997)
This article discusses the implementation of equal pay law in the European Union and particularly in the United Kingdom. In addition to examining the current legal framework it considers possible developments of equal pay law in the United Kingdom and at European Union level given recent changes in the political environment.